Giant Pheochromocytoma Diagnosis Confounded by Amphetamine Use - Shreya Amin; Matthew Gilbert; Kaitlyn Barrett (Case Reports in Endocrinology)
Objective. Diagnosis of giant pheochromocytoma is difficult; patients often lack the classic triad and presence of gross biochemical positivity. At times, presence of sympathetic stimulant drugs can further complicate the clinical picture. Here, we present a case of giant “functional” pheochromocytoma with a history of amphetamine use. Case Description. 37-year-old female presented with a 1-day history of abdominal pain. CT abdomen identified a 12.5 cm heterogeneously enhancing left adrenal mass. Plasma/urine catecholamine and metanephrine levels were markedly elevated with evidence of elevated serum/urine cortisol. However, the patient’s subsequent urine toxicology was found to be positive for amphetamines, which she later admitted to using, 1 week prior to admission. Repeat biochemical workup after 1 week drug washout period showed improvement in both catecholamine and cortisol levels. Given the high degree of suspicion for PCC, an open laparoscopic adrenalectomy was performed with histology confirming SDHB gene mutation positive giant pheochromocytoma. Discussion. Diagnosis of PCC in a patient with a history of amphetamine abuse remains an enigma, to which addition of it being a giant PCC that are rare and typically silent further confounds the clinical picture as seen in this case. Conclusion. PCC could be termed a “chameleon” tumor given its varied clinical presentations and lack of standardized biochemical and radiological data (giant, pheochromocytoma, and amphetamine).